Redesigning Mobile Human-Resource Management in Small and Medium Enterprises - Daniel Hadrian Yohandy; Parjanto Parjanto; Flourensia Sapty Rahayu (Universitas Airlangga, 2018)
Small and Medium Enterprises (SMEs) in Indonesia continue to grow because it is supported by ideas and creations of the community that keep creating new idea either from food products, clothing, or multipurpose tools. There are already a few examples of successful IT implementation on SME in many countries, but in Indonesia, many SME's does not yet know about the benefit of IT implementation in their businesses. To solve this problem SME's need for learning and adapting IT from the internal functions of the organization, and one of them is Human Resource Management (HRM). This research will try to redesign HRM system based on mobile system or smartphones as one of most popular and most used technology in Indonesia. Smartphones can be used as an early and easy approach for those SME's in the IT-based system. This research will be focused on collecting qualitative data based on the interview with 5 respondents as owner or manager of SME to specify requirements of the design and problems that can be solved. As for the results, the major problem is from the human resource which is lack of knowledge, experience and there are few internal problems in SME's which can be solved by redesigning the mobile system. After presenting the result of redesigning, respondents conclude that the system is sufficient for their daily business activities and they feel comfortable with the design on the mobile system as they said it is easy to understand. Presented design can be much improved by adding more information, opinion, and feedback from other SMEs into consideration in the aim to achieve effective and efficient system design.